A highly active and stable palladium catalyst on a g-C3N4 support for direct formic acid synthesis under neutral conditions. Issue 99 (24th November 2016) - Park, Hunmin; Lee, Ju Hyung; Kim, Eun Hyup; Kim, Kwang Young; Choi, Yo Han; Youn, Duck Hyun; Lee, Jae Sung
Abstract : Graphitic carbon nitride (g-C3 N4 ) is applied as a support of the Pd catalyst for direct HCOOH synthesis by CO2 hydrogenation under neutral conditions. Abstract : Graphitic carbon nitride (g-C3 N4 ) is applied as a support of the Pd catalyst for direct HCOOH synthesis by CO2 hydrogenation under neutral conditions. The high CO2 affinity of g-C3 N4 is responsible for the enhanced catalytic activity and stability relative to the inert support such as a carbon nanotube.